(untitled) (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2024)
Parents have an important role in efforts to fulfill toddler’s nutrition, especially mothers who are the main caregivers of children. Mothers’ knowledge regarding good nutritional intake for toddler influences parents’ attitudes in choosing and processing food so that the nutritional intake obtained by toddler will be more optimal. The results of interviews conducted with mothers of toddlers by PKL students showed that 100% of mothers in Banjar Dinas Dauh Pura had insufficient knowledge regarding toddler nutrition. This service was carried out on 25 mothers of toddlers in Banjar Dinas Dauh Pura, Panji Village, Sukasada District, Buleleng Regency, Bali in November 2023 using lecture and discussion methods using power point and video media. The aim of this activity is to increase the knowledge of mothers of toddlers regarding fulfilling toddler nutrition. Measuring the achievement of service goals is carried out using a pretest before counseling and a posttest after counseling. The evaluation results showed that mothers’ knowledge regarding nutritional needs for toddlers increased significantly after being given counseling.